2011
DOI: 10.5897/ajb10.145
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of aluminium on the seedling parameters of wheat

Abstract: In order to determine the effect of different aluminium (Al) concentrations on the seedling parameters of wheat and the effect of malate and citrate treatments as chelates for reducing the noxious effect of Al in medium culture and seedlings of two wheat cultivars, Darab (Al sensitive) and Maroon (Al tolerant) were grown on hydroponic solution (non modified Hoagland) containing AlCl 3 (0-100-200-300 μM). Factorial experiment was realized in a complete randomized design with three replications. The root and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…They concluded that among the superoxide dismutase, ascorbate peroxidase (APX), catalase (Cat), and glutathione-S-transferase (GST) enzymes induced by Al stress, catalase and GST may play an important role in the detoxification of reactive oxygen species in Al-tolerant wheat plants. Two wheat cultivars, Darab (Al-sensitive) and Maroon (Al-tolerant) grown on hydroponic solution were used in assessing growth of wheat seedlings under Al stress (Nasr et al, 2011). Results revealed that, for fresh weight of root, fresh weight of shoot, dry weight of shoot and length of root, Al concentrations and their interaction with cultivar were highly significant.…”
Section: Wheat (T Aestivum L)mentioning
confidence: 99%
“…They concluded that among the superoxide dismutase, ascorbate peroxidase (APX), catalase (Cat), and glutathione-S-transferase (GST) enzymes induced by Al stress, catalase and GST may play an important role in the detoxification of reactive oxygen species in Al-tolerant wheat plants. Two wheat cultivars, Darab (Al-sensitive) and Maroon (Al-tolerant) grown on hydroponic solution were used in assessing growth of wheat seedlings under Al stress (Nasr et al, 2011). Results revealed that, for fresh weight of root, fresh weight of shoot, dry weight of shoot and length of root, Al concentrations and their interaction with cultivar were highly significant.…”
Section: Wheat (T Aestivum L)mentioning
confidence: 99%